1993
DOI: 10.1200/jco.1993.11.4.638
|View full text |Cite
|
Sign up to set email alerts
|

Role of computed tomography in the staging of primary melanoma.

Abstract: Body CT is not a useful imaging study in the detection of occult metastases in patients with primary melanoma. Although body CT commonly shows suspicious radiologic abnormalities in patients with early melanoma, these abnormalities most likely represent benign processes or a second primary tumor, rather than metastatic melanoma. The value of body CT in patients who present with nodal metastases needs further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
3
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 8 publications
2
62
3
4
Order By: Relevance
“…Our results and those of others suggest that the widespread use of CT imaging should be reserved for patients whose findings on history and physical exam are suspicious for the presence of regionally advanced or systemic disease. Buzaid et al 3 examined the role of CT scans in the initial workup of stage I, II, or III melanoma patients (including some patients with palpable lymph nodes). In their study, imaging ultimately identified true-positive findings in 2 of 151 (1.3%) patients, whereas false-positive findings for melanoma were identified in 18% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results and those of others suggest that the widespread use of CT imaging should be reserved for patients whose findings on history and physical exam are suspicious for the presence of regionally advanced or systemic disease. Buzaid et al 3 examined the role of CT scans in the initial workup of stage I, II, or III melanoma patients (including some patients with palpable lymph nodes). In their study, imaging ultimately identified true-positive findings in 2 of 151 (1.3%) patients, whereas false-positive findings for melanoma were identified in 18% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,12,14,15 Finally, the sample size of our study was limited to 158 patients, and the subgroup analyses were even more limited in size.…”
mentioning
confidence: 99%
“…Also in treated patients, detection of recurrences or of metastases is made difficult by the wide range of potential hematogenous spread of the tumour. This requires regular chest, abdomen, pelvis and brain CT or MRI, as well as confirmatory procedures in cases of indeterminate or suspicious results [262].…”
Section: Melanomamentioning
confidence: 99%
“…In an attempt to detect these occult lesions, an initial staging evaluation is often performed on patients newly diagnosed as having melanoma. While a detailed medical history taking and physical examination are essential for this purpose, there are few data to support the use of screening studies such as chest xray films, [3][4][5][6][7] computed tomographic (CT) scans, 8,9 liver-spleen scans, [3][4][5][6][10][11][12] bone scans, [3][4][5][6]10,11 and brain scans [3][4][5][6][10][11][12] in asymptomatic patients. Despite this, the initial workup for patients with localized melanoma often includes multiple diagnostic studies, most frequently chest radiography.…”
mentioning
confidence: 99%